Expansion of the tetracycline resistome in Aeromonas salmonicida with a tet(D) gene found in plasmids pAsa-2900 and pAsa-2900b - Girard, Sarah B.; Marcoux, Pierre-Étienne; Paquet, Valérie E.; Zoubaï, Sahra; Can, Thuy Nhu Vy; Attéré, Sabrina A.; Vincent, Antony T.; Charette, Steve J. (Frontiers in Bacteriology, 2024)
Plasmids carrying antibiotic resistance genes occur frequently in Aeromonas salmonicida subsp. salmonicida, an aquatic pathogen. In this study, we describe three new plasmids found in strains of A. salmonicida subsp. salmonicida from Québec, Canada: pAsa-2358, pAsa-2900, and pAsa-2900b. The last two plasmids have a tet(D) resistance gene against tetracycline, which has not been previously found in A. salmonicida. The only difference between these two plasmids is the presence of a florfenicol resistance gene (floR) surrounded by two copies of the same insertion sequence, indicating that pAsa-2900 and pAsa-2900b are plasmid variants. All three plasmids represent an issue for aquaculture because they bear resistance genes against antibiotics used to treat infected fish: floR and tet(A) for pAsa-2358; floR, sul2, and tet(D) for pAsa-2900; and sul2 and tet(D) for pAsa-2900b. Conjugation assays confirmed that the three plasmids are capable of conjugation with one A. salmonicida mesophilic strain, one A. hydrophila strain, and Escherichia coli DH5α; except for pAsa-2358 that is not able to conjugate into E. coli DH5α. Based on the results of antibiotic resistance assays, the tet(D) gene provides a greater resistance to tetracycline than the tet(A) gene found in many A. salmonicida subsp. salmonicida plasmids. This is the case whether the plasmids are in their parental A. salmonicida subsp. salmonicida strains or in Aeromonas sp. transconjugates. The presence of these three plasmids in A. salmonicida subsp. salmonicida strengthens the role of this bacterium as a reservoir for antibiotic resistance genes.